2019
DOI: 10.1002/csr.1742
|View full text |Cite
|
Sign up to set email alerts
|

Does religion benefit corporate social responsibility (CSR)? Evidence from China

Abstract: Corporate social responsibility (CSR) has been attracting ever considerable attention from practice and academia, but the determinants of CSR remain unclear, especially in transitional economies. Using firm-level data of listed firms in China and constructing the variable of religion through the geographic proximity method, this study investigates the relationship between religion and CSR and further explores the differences between low-and high-polluting industries. Our empirical results demonstrate that reli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
88
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(98 citation statements)
references
References 73 publications
(131 reference statements)
7
88
0
3
Order By: Relevance
“…The GOEL president orientation toward sustainability is not a merely cosmetic approach; instead, it is an ethical orientation, proper to sustainable entrepreneurs. This has to be ascribed to his strong religious values that allow him to believe that structural contextual problems could be faced through the cooperation tool (Liao, Dong, Weng, & Shen, ; Su, ). The personal history of the GOEL president, who founded GOEL together with the bishop of Locri and Gerace Diocese (Mons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The GOEL president orientation toward sustainability is not a merely cosmetic approach; instead, it is an ethical orientation, proper to sustainable entrepreneurs. This has to be ascribed to his strong religious values that allow him to believe that structural contextual problems could be faced through the cooperation tool (Liao, Dong, Weng, & Shen, ; Su, ). The personal history of the GOEL president, who founded GOEL together with the bishop of Locri and Gerace Diocese (Mons.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, educators should enable students to develop a deep "passion" for sustainability in order to educate not just future business leaders but future global citizens (Adams, Heijltjes, Jack, Marjoribanks, & Powell, 2011). The strong, true religious values of the GOEL president affect the GOEL normative CSR strategy (Su, 2019;Liao et al, 2019) and his transformational leadership empowers his employees (Felício et al, 2013).…”
Section: Considering Conclusionmentioning
confidence: 99%
“…Authors have ascribed this result to the competitive impacts of formal institutions and informal institutions on corporate behavior (Ali et al, 2017; Ali & Frynas, 2018; Du et al, 2016; Tolmie, Lehnert, & Zhao, 2020). Focusing on firms from the same country, Su (2019) has shown that religiosity leads managers to be less selfish and to take better care of stakeholders. The more positive relationship between the management of companies located in highly religious areas, society, and other stakeholders leads to stronger corporate social responsibility behaviors.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 99%
“…These alternative terms are illustrated in Figure 4. These conceptual synonyms for “DO” contained in Figure 4 stem from the development economics discipline which explains the adoption of alternative terms such as Transitional Economies (Su, 2019; Zheng et al, 2014) and Bottom Billion or Bottom/Base of the Pyramid (Blowfield & Dolan, 2014; Hong & Park, 2020; Marconatto et al., 2017).…”
Section: Results: Diagnostic Presentation and Discussionmentioning
confidence: 99%